Association of Vitamin D Deficiency with Increased Pulse Wave Velocity and Augmentation Index in Children With Chronic Kidney Disease (Iranian Journal of Kidney Diseases, 2018)
Introduction. It is known that in children with chronic kidney disease (CKD), cardiovascular damage starts in the form of arterial stiffness. There are risk factors other than the traditional ones such as arterial stiffness hypertension, obesity, hypercholesterolemia, and insulin resistance. Vitamin D deficiency is rather common in CKD, and it was introduced as a risk factor for atherosclerosis; however, its relationship with arterial stiffness is not known completely. The purpose of this study was to research the relationship between 25-hydroxyvitamin D levels and arterial stiffness. Materials and Methods. Arterial stiffness was evaluated by measuring augmentation index (AI) and pulse wave velocity (PWV) from the radial and carotid arteries with a Vicorder. The 25-hydroxyvitamin D levels were measured by an immunoassay method. Results. In the 81 CKD patients (mean age, 13.21 ± 6.02 years; mean body mass index, 19.42 ± 5.12 kg/m2; and 56.8% male), the mean vitamin D level was 60.71 ± 39.52 ng/mL, the mean AI was 7.93 ± 7.77%, and the mean PWV was 9.79 ± 4.36 m/s. Serum levels of 25-hydroxyvitamin D was correlated with AI (r = -0.482, P = 0.001) and PWV (r = -0.57, P = .001). Conclusions. In this study, it was proven that vitamin D deficiency in children was related to nondiabetic and nondialysis CKD.